Are the Benefits of Export Support Durable? : Evidence from Tunisia - Cadot, Olivier; Fernandes, Ana M.; Gourdon, Julien; Mattoo, Aaditya (Elsevier, 2016)
This paper evaluates the effects of the FAMEX export promotion program in Tunisia on the performance of beneficiary firms. While most studies assess only the short-term impact of such programs, we consider also the longer-term impact. Our estimates suggest that the average beneficiary initially saw both higher overall export levels and greater diversification across destinations and products. However, three years after the intervention, beneficiaries' export levels and diversification were no longer significantly different from those of a control group. Furthermore, the effects were heterogeneous across firms: small and large firms saw no positive impact on export levels, and even the positive impact on medium sized firms was temporary. The temporariness of the impact was not due to spillovers to non-beneficiary firms which helped them to catch up, or to greater exposure of beneficiaries to crisis-affected economies. Rather, the impact may be transient because the program did not lead to the enhancements in product quality or sophistication which could have strengthened competitiveness durably. Notwithstanding its transient effect, the relatively low-cost FAMEX still generated two Tunisian Dinars of private profits per Dinar of program expenditure, and the additional corporate tax revenue just covered the public cost of the program.